Faktor Utama Keterlambatan Pembayaran Dalam Proyek Perumahan Subsidi dan Komersial - Verel, Bunga Olivia; Milyardi, Roi; Lesmana, Cindrawaty (Kadiri University, 2024)
In the implementation of housing development, the problem of late payment delays is a common issue encountered in commercial and subsidized housing projects during construction. These delays impact the timely completion and lead to disputes among the involved parties, which include owners, contractors, and subcontractors. This study aims to analyze the primary factors contributing to late payment in construction projects, specifically in commercial and subsidized housing. The analysis is conducted from the perspective of the owner, contractors, and subcontractors. The study involves six owner respondents, six contractor respondents, and four subcontractor respondents. The survey results were analyzed using the Analytical Hierarchy Process (AHP) to assess the significance of various factors influencing payment delays in both housing schemes. The analysis results indicate that financial issues with the owner's company are crucial factors from the owner's perspective in causing payment delays in both commercial and subsidized housing projects. A major challenge faced by contractors is the lack of capital availability, which can lead to delays that affect all involved parties. Meanwhile, discrepancies between job specifications not following the contract from the subcontractor's viewpoint highlight the importance of clear communication and rigorousness. All parties involved in housing projects need to improve financial management, enhance capital procurement, and tighten the supervision of contract implementation. By identifying key factors, adopting best practices can help mitigate the risk of payment delays and improve efficiency in future housing project implementations, whether commercial or subsidized.